Mehrsprachigkeit und Plurikulturalität im fremdsprachlichen Diskurs. : Zum didaktischen Potenzial von Linguistic Landscapes in Deutsch als Fremdsprache - Baumann, Beate (Linguistik Online, 2025)
This article will explore the possibilities of working with texts in public spaces. This will be discussed against the background of the sociolinguistic research field of linguistic landscapes with the aim of sensitising learners to consciously perceive the linguistic diversity of their surroundings and encouraging them to reflect on the distribution of languages, their functions and their social significance. In particular, the didactic project “Visual multilingualism and multiculturalism in urban areas. ‘Spot German’ in Catania” is intended to illustrate how the students can initiate linguistic and culturally reflective learning processes through their encounter with German-speaking traces in their surroundings, which can be made fruitful for the development of intercultural and symbolic competences.